Satisfaction with telemedicine-delivered inflammatory bowel disease care depends on disease activity, personality and economic factors. Issue 2 (27th September 2022) - Storan, Darragh; Lavelle, Joseph; Burke, Anne-Marie; Hamzawi, Mary; Brett-Kilmurray, Orna; De Dominicis, Noemi; McHugh, Louise; Mulcahy, Hugh E
Abstract : Objective: Patients with inflammatory bowel disease (IBD) traditionally receive follow-up care at face-to-face outpatient clinics. During the COVID-19 pandemic, gastroenterology societies recommended IBD clinics to be carried out remotely where possible using telephone or telemedicine-delivered virtual clinics. Previous studies have demonstrated patient satisfaction with virtual clinics but few studies have examined factors that impact satisfaction or assessed patient's personal perception of the virtual clinic experience. Design/method: Patients who had their IBD clinic appointment changed from face-to-face to telephone virtual clinic completed a questionnaire relating to their clinical experience and preference for future care. Qualitative data were also collected and evaluated using content analysis to identify major themes associated with the patient experience. Results: 141 patients were included for analysis. The virtual clinic satisfaction questionnaire was found to be valid while patients expressed high-satisfaction levels with virtual clinics (median satisfaction score 18, range 0–20). Multivariate analysis identified open personality type (p=0.004), short disease duration (p=0.047) and higher cost to attend clinic (p=0.047) as predictors of high-satisfaction levels, with active disease (p=0.035) and an agreeable personality type (p=0.042) associated with low satisfaction levels. Content analysis of the qualitative data identified three major themes connected to virtual clinic convenience, lack of physical interaction and disease activity. Conclusion: Patients expressed high levels of satisfaction with telemedicine-delivered IBD clinics, with most wishing to continue their use. Personality type should be recognised as an important variable affecting clinical satisfaction, in addition to socioeconomic and disease-related factors.